Distinct mediating patterns between metal filtering and species coexistence of rare and abundant subcommunities in heavily polluted river sediments - Min Wang; Wei Zhang; Zhi Dong; Zirou Yang; Junying Zhao; Xiaoyu Guo (Environment International, 2023)
It is unknown how anthropogenic pollutants released into freshwater ecosystems affect the assembly processes of microbial communities in river sediment. We used high-throughput sequencing to examine the assembly of rare and abundant subcommunities in a heavily polluted urban river: the Beiyun River in Beijing, China. Although deterministic processes overrode stochastic processes in shaping local rare and abundant subcommunities, there were distinctly different assembly mechanisms of rare and abundant subcommunities. Rare subcommunity assembly was governed more by interspecific interactions, and environmental selection and dispersal limitation explained only a small fraction of the variation. However, both factors seemed to govern the assembly of abundant subcommunities. Our results implied that microbial co-occurrence associations tended to be higher when rare subcommunities were less driven by community assembly, and that these associations tended to be lower when abundant subcommunities were more driven by community assembly. A balance between the community assembly and species coexistence was exhibited at the subcommunity level. Importantly, we tried to disentangle the assembly process of abundant subcommunities into introduction and colonization processes characterized by the presence/absence and relative abundance datasets. Interestingly, metals explained the highest percentage of spatial variation in the species introduction process. By affecting nutrient availability, metals also shaped the abundant subcommunity in the species colonization process, but this did not surpass nutrient availability. Therefore, disentangling the introduction and colonization processes enhances our understanding of the assembly mechanisms of microbial communities in heavily polluted running water ecosystems at fine geographical scales.